Study on the clinical characteristics, persistent infection capability and viral load of human papillomavirus type 26 single infection - Zuyi Chen; Xiaoyang Li; Di Tian; Jingchi Liu; Xia Bai; Tingting Feng; Shiqi Chen; Lin Chen; Qiongyao Li (Virology Journal)
Abstract Background Human papillomavirus (HPV) infection is the main cause of cervical cancer. Different types of HPV have varying carcinogenic capabilities, and viral load is one of the key indicators of pathogenicity. Currently, there is a lack of clinical data on HPV26. This study analyzed the clinical characteristics of patients with HPV26 single infection. Methods Exfoliated cervical cells were collected for HPV genotyping from women who attended gynecological outpatient clinics or physical examinations. The clinical characteristics of HPV26 single infections in both cross-sectional and follow-up studies were examined, and the association of viral load with HPV26 persistent infection and pathogenicity was investigated. Results The HPV26 positive rate among women visiting hospitals for gynecological medical consultation or physical examination was approximately 0.09% (379/435,072). Among the HPV types tested, the detection rate of HPV26 was 0.37% (379/103,608). In the cross-sectional histopathological study of 101 patients with HPV26 single infection, 62.37% (63/101) presented lesion-free. The numbers of patients with cervical intraepithelial neoplasia (CIN) 1, CIN2, and CIN3 were 25, eight, and five, respectively. Cervical cancer was not detected in any patient. 71 patients attended follow-up examinations as well as HPV26 retesting up to two years, during which, 28.57% (6/21) of CIN1 patients have developed into high-grade lesions, and 9.61% (5/52) of lesion-free patients have progressed to CIN stage. The viral load in the CIN group was significantly higher than that in the lesion-free group (p = 0.012). Similarly, the viral load in the persistent infection group was significantly higher than that in the viral-clearance group (p < 0.001). Conclusions The pathogenicity of single HPV26 infections is moderate among high-risk types, warranting the inclusion of HPV26 in expanded screening for HPV. High viral load is an important factor in the persistent infection and pathogenicity of HPV26. Viral load is expected to serve as a screening risk factor for persistent infection and disease progression associated with HPV26.